2015
DOI: 10.1073/pnas.1406689112
|View full text |Cite
|
Sign up to set email alerts
|

Crop rotations in the sea: Increasing returns and reducing risk of collapse in sea cucumber fisheries

Abstract: Rotational harvesting is one of the oldest management strategies applied to terrestrial and marine natural resources, with crop rotations dating back to the time of the Roman Empire. The efficacy of this strategy for sessile marine species is of considerable interest given that these resources are vital to underpin food security and maintain the social and economic wellbeing of small-scale and commercial fishers globally. We modeled the rotational zone strategy applied to the multispecies sea cucumber fishery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…To overcome this issue, empirical data could be combined with population modelling to assess the potential of PHCs for long‐term sustainability of fish stocks and conservation (Carvalho et al., ). This would also allow for the assessment of long‐term fisheries benefits and whether effort displacement following PHC implementation may lead to overharvesting in the nearby areas open to fishing, an issue that is currently in debate with rotational fisheries (Game, Bode, McDonald‐Madden, Grantham, & Possingham, ; Kaplan, Hart, & Botsford, ; Plagányi, Skewes, Murphy, Pascual, & Fischer, ; Plagányi et al., ; Purcell, Uthicke, Byrne, & Eriksson, ).…”
Section: Discussionmentioning
confidence: 99%
“…To overcome this issue, empirical data could be combined with population modelling to assess the potential of PHCs for long‐term sustainability of fish stocks and conservation (Carvalho et al., ). This would also allow for the assessment of long‐term fisheries benefits and whether effort displacement following PHC implementation may lead to overharvesting in the nearby areas open to fishing, an issue that is currently in debate with rotational fisheries (Game, Bode, McDonald‐Madden, Grantham, & Possingham, ; Kaplan, Hart, & Botsford, ; Plagányi, Skewes, Murphy, Pascual, & Fischer, ; Plagányi et al., ; Purcell, Uthicke, Byrne, & Eriksson, ).…”
Section: Discussionmentioning
confidence: 99%
“…Fisheries benefits from temporal or rotational closures through the build-up of abundance and biomass have primarily been demonstrated for sessile or sedentary invertebrates (e.g., Hart 2003, Valderrama and Anderson 2007, Plagányi et al 2015. While such benefits are predicted for reef fish (De Klerk andGatto 1981, Game et al 2009), these have only been demonstrated in a few cases (Cinner et al 2006, Bartlett et al 2009, Jupiter et al 2012.…”
mentioning
confidence: 99%
“…The alternating fishing ban (Dunn et al, 2011;Rassweiler et al, 2012;Russo et al, 2014b;Plagányi et al, 2015) can be considered a management strategy that, given a feasible control in the harbors-as for the seasonal fishing ban-could efficiently change the exploitation pattern, thereby redirecting the fishing activity toward biggest individuals and making the harvest strategy more viable. Indeed, this alternating fishing ban could produce a less severe impact on landings and revenues than the seasonal fishing ban does, while having almost the same effect on the improvement in the SSB and reducing the proportion of smaller individuals, which are less profitable in the market.…”
Section: Discussionmentioning
confidence: 99%